Edukasi Keuangan melalui Program Sosialisasi di Desa Parit Keladi - Yulianto, Rifky Syahputra; Jaya, Arman; Basima, Afra; Verizki, Chita; Lovianda, Visi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Financial education programs, particularly those focusing on the importance of saving from an early age, have become one of the flagship initiatives in the Student Community Service (KKM) activities in Parit Keladi Village. These programs, particularly focusing simple financial management concepts. The outreach is conducted through interactive methods that involve educational games and the provision of rewards to enhance interest and participation. The results of this program demonstrate an increased awareness among children regarding the importance of saving, as well as their ability to distinguish between needs and wants. This article further discusses the significance of saving from a young age and how this program has been implemented within the context of the Parit Keladi community.